Kajian Beberapa Aspek Botani Anggrek Endemik Coelogyne celebensis J.J. Sm. dari Taman Nasional Lore Lindu Sulawesi Tengah - Ramadhanil Ramadhanil (Biocelebes, 2010)
A research about the study on some botanical aspects of an endemic orchid Coelogyne celebensis J.J.Sm from Lore Lindu National Park has been conducted from March to November 2009. The research was located at the western part of Lore Lindu National Park, Herbarium Celebense (CEB) UNTAD, Orchid house of Bogor Botanic Garden, and the Herbarium Bogoriense (BO) Cibinong West Java. The survey method in the field was used to collect the living material of Coelogyne celebensis J.J.Sm, and then the description of the orchid was done at the Herbarium Celebense (CEB), Herbarium Bogoriense and Bogor Botanic Garden. The data of some botanical aspects included morphological characteristics, ecological (bitoik and abiotik) factor and social economic of the community who living around the habitat of the orchids were presented. Key words: Endemic orchid, botanical aspect, Coelogyne celebensis J.J.Sm, Lore Lindu NP.